Teacher orientations in climate change education - Favier, Tim; Duindam, Yaël; Wansink, Bjorn; Beneker, Tine (Carfax Publishing Ltd., 2024)
The question what the focus of climate change education should be has been debated by academics and policy makers. However, this debate is informed to only a limited extent by empirical research on the position of teachers. Based on interviews with nineteen experienced secondary geography teachers in the Netherlands, nine orientations were distinguished, ranging from transmissive to transformative, and from instrumental to emancipatory. The teachers generally found knowledge important as a basis for forming an opinion or making decisions. Many wanted to make students aware that anthropogenic climate change is a fact, as they saw it as a settled issue. However, teachers varied in their opinions regarding sustainable values and behaviour. One teacher advocated sustainable values, while five only wanted to stimulate sustainable behaviour by steering indirectly. The majority focused on well-considered behaviour, but many teachers still provided incentives. Beliefs about the neutrality of education played a major role.
Keywords: Climate change; PCK; normativity; orientation; sustainability; teacher perspective; Taverne; Education; SDG 13 - Climate Action